Overview of Job Satisfaction and Flexibility on Employee Performance - Mustakim, Jamal (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
Behind the performance achievement there are many benefits received by the company, including progress, achieving goals, increasing work productivity, maintaining management systems, increasing purchases and the number of customers. Therefore, performance gets more attention, as a principle in the organization. However, performance does not stand alone, there are many factors that influence it, including the level of satisfaction and the work system. This study was made, to see a causal relationship, between job satisfaction and flexibility with performance. To test this statement, this research uses quantitative methods. As for the disclosure, multiple regression statistical analysis is used with estimation and determination tests. The subjects of this research are employees in the technology and information department of the Teltranet Application Solusi company, Jakarta. Data were collected through a questionnaire distribution using an attitude measurement scale / Likert. The number of research informants as many as 67 functional employees (non-structural). The results of the regression test explain that performance can be positively and significantly strengthened, if employee satisfaction increases. Likewise with work flexibility, there is a positive trend and a significant effect on performance. This finding confirms that a good mood as well as an easy/flexible work system can strengthen employee productivity and work results.